Antiangiogenic Therapy for Glioma - Cea, Valentina (Hindawi Publishing Corporation, 2012)
Currently, antiangiogenic agents are routinely used for the treatment of patients with glioma. However, despite advances in pharmacological and surgical therapy, glioma remains an incurable disease. Indeed, the formation of an abnormal tumor vasculature and the invasion of glioma cells along neuronal tracts are proposed to comprise the major factors that are attributed to the therapeutic resistance of these tumors. The development of curative therapeutic modalities for the treatment of glioma requires further investigation of the molecular mechanisms regulating angiogenesis and invasion. In this review, we discuss the molecular characteristics of angiogenesis and invasion in human malignant glioma, we present several available drugs that are used or can potentially be utilized for the inhibition of angiogenesis in glioma, and we focus our attention on the key mediators of the molecular mechanisms underlying the resistance of glioma to antiangiogenic therapy.